Regulation of MYC gene expression by aberrant Wnt/β-catenin signaling in colorectal cancer - Rennoll, Sherri (World J Biol Chem, 2015)
The Wnt/β-catenin signaling pathway controls intestinal homeostasis and mutations in components of this pathway are prevalent in human colorectal cancers (CRCs). These mutations lead to inappropriate expression of genes controlled by Wnt responsive DNA elements (WREs). T-cell factor/Lymphoid enhancer factor transcription factors bind WREs and recruit the β-catenin transcriptional co-activator to activate target gene expression. Deregulated expression of the c-MYC proto-oncogene (MYC) by aberrant Wnt/β-catenin signaling drives colorectal carcinogenesis. In this review, we discuss the current literature pertaining to the identification and characterization of WREs that control oncogenic MYC expression in CRCs. A common theme has emerged whereby these WREs often map distally to the MYC genomic locus and control MYC gene expression through long-range chromatin loops with the MYC proximal promoter. We propose that by determining which of these WREs is critical for CRC pathogenesis, novel strategies can be developed to treat individuals suffering from this disease.